Lasius umbratus - Collingwood, C. A. (Zenodo, 1979)
38. Lasius umbratus (Nylander, 1846) Figs. 139-142. Formica umbrata Nylander, 1846b: 1048. Worker. Clear yellow to reddish yellow; funiculus segments 2 to 4 slightly longer than wide. Scape elliptical in cross section. Petiole tapering to dorsal crest which is usually emarginate. Body surface and appendages covered in adpressed silvery pubescence. Longest hairs on gaster 0.06 mm to 0.11 mm, about half maximum hind tibial width. Erect hairs on genae, scapes and tibiae numerous. Length: 3.8-5.5 mm. Queen. Reddish brown. Head broader than maximum width of alitrunk. Funiculus segments longer than broad. Petiole sides curved, tapering to dorsal crest which is more or less emarginate. Pubescence and body hairs as in worker. Head width: 1.65-1.80 mm. Length: 6.8-8.0 mm. Male. Dark brown to brownish black. Head broad with denticulate mandibles. Petiole somewhat tapering. Body surface including frons with rugose microsculpture and generally thick pubescence. Eyes with outstanding hairs. Tibial and scape hairs variable often sparse. Length: 4.0-4.8 mm. Distribution. Local in Denmark and Southern Fennoscandia up to 62°. Throughout British Isles to Central Scotland. - Range: throughout Europe, widely distributed and not uncommon. Biology. This species nests under boulders, in tree stumps and at the base of old trees. Workers are subterranean and seldom or never seen above ground. Flight period from mid August to late September. Single queens found colonies by invasion of and adoption in Lasius niger, L. alienus or occasionally L. brunneus nests. In late summer dealate queens often wander over the surface of L. niger nests, sometimes carrying a dead L. niger worker as a prelude to securing adoption. Published as part of Collingwood, C. A., 1979, The Formicidae (Hymenoptera) of Fennoscandia and Denmark., pp. 1-174 in Fauna Entomologica Scandinavica 8 on pages 101-102